Medical photography: ethics, consent and the intersex patient - Creighton, S; Alderson, J; Brown, S; Minto, C L (BJU international, 2002)
In this review we discuss the effects that photography may have on the patient and present information obtained from our intersex services and research.
Keywords: LGBTQIA2+; corps; cours; discipline; gynécologie; identités LGBTQIA2+; lit4700; photographie médicale; premier cycle; ressource en ligne; sciences; thématiques; éthique